Clinical research in communication disorders : principles and strategies - Hegde, M. N. (Mahabalagiri N.); Salvatore, Anthony P. (Plural Publishing, 2021)
This thoroughly updated fourth edition of Clinical Research in Communication Disorders: Principles and Strategies remains an instrumental resource for courses on research methods and design in communication disorders. The book is separated into three key sections: science and the scientific methods, clinical research designs, and doing, reporting, and evaluating research. Together, these sections provide thorough coverage of both the single-subject and group design strategies along with issues of measurement; philosophy of science; ethics of research; and planning, conducting, and reporting research. Instructors and students in communication sciences and disorders will appreciate the text's comprehensive coverage of scientific methods, group and single-subject research designs, report writing, and ethics of research in a single source.